Towards a pain-free life for the elderly: The role of physiotherapy in low back pain prevention education - Siti Muawanah; Ratih Ayuningtiyas; Brilian Dini MaIballa; Siti Juariah (Community Empowerment, 2024)
Low Back Pain (LBP) sufferers often experience sharp pain triggered by certain postures or movements, which improves after rest and worsens after activity. Signs of inflammation such as heat, discoloration, or swelling are rarely observed. The aim of this activity is to provide appropriate education on treatment to prevent increased pain and changes in posture due to LBP, by offering Neuromuscular Taping (NMT) Treatment and William flexion exercises. This activity employs various approaches, including Focus Group Discussion (FGD) and distribution of leaflets on the role of physiotherapy in LBP education and prevention, as well as educational interventions on neuromuscular taping application and William flexion exercises. This activity yields significant benefits for the health and well-being of LBP sufferers, evidenced by a substantial reduction in pain (p<0.001), with a mean VAS score decreasing from 6.93 ± 0.73 before treatment to 4.07 ± 0.83 after treatment.